Inhibitory Effects of Eucalyptus and Banaba Leaf Extracts on Nonalcoholic Steatohepatitis Induced by a High-Fructose/High-Glucose Diet in Rats. (27th April 2015) - Takahashi, Yoshihisa; Sugimoto, Keiichiro; Soejima, Yurie; Kumagai, Arisa; Koeda, Tatsuki; Shojo, Aiko; Nakagawa, Kazuya; Harada, Naoki; Yamaji, Ryoichi; Inui, Hiroshi; Yamanouchi, Toshikazu; Fukusato, Toshio
Abstract : Nonalcoholic steatohepatitis (NASH) is a liver disease associated with metabolic syndrome. The aim of this work was to examine whether eucalyptus ( Eucalyptus globulus ) leaf extract (ELE) and banaba ( Lagerstroemia speciosa L.) leaf extract (BLE) inhibited NASH induced by excessive ingestion of fructose in rats. Wistar rats were divided into four groups according to four distinct diets: starch diet (ST), high-fructose/high-glucose diet (FG), FG diet supplemented with ELE, or FG diet supplemented with BLE. All rats were killed after 5 weeks of treatment. Serum alanine aminotransferase and total cholesterol levels were significantly lower in the BLE group than in the FG group. Liver histopathology, including steatosis, lipogranulomas, and perisinusoidal fibrosis, was significantly attenuated in the ELE and BLE groups compared with the FG group. Levels of 2-thiobarbituric acid reactive substances (TBARS), which reflect oxidative injury to the liver, were significantly suppressed by ELE and BLE. Western blotting analysis indicated that interleukin-6 expression levels were significantly lower in the ELE and BLE groups than in the FG group. These results suggest that ELE and BLE reduced lipogenesis, oxidative stress, and inflammatory cytokine expression and thus inhibited NASH induced by excessive ingestion of fructose in rats.